An Experimental Study on Mechanical Properties and Fracture Characteristics of Saturated Concrete under Coupling Effect of Low Temperature and Dynamic Load. (20th September 2022) - Wang, Mengxiang; Zong, Qi; Wang, Haibo
Abstract : Concrete is widely used in bridge foundation, water supply, and drainage engineering. On the one hand, the saturated concrete is always in the saturated state. In the cold winter, northeast China and the alpine region suffer from freezing disaster. On the other hand, it has to continue to bear the dynamic load action of vehicles and running water, which makes the stress state of saturated concrete more complicated under the coupling action of low temperature and dynamic load. In order to study the mechanical properties and fracture characteristics of saturated concrete under the coupling effect of low temperature and dynamic load, the impact compression tests of concrete under normal temperature 20°C, -5°C, -10°C, and -15°C were carried out with a diameter of 74 mm split Hopkinson pressure bar (SHPB). The stress-strain characteristics, energy dissipation, and failure modes of specimens under different low temperatures were studied. From a detailed point of view, the failure mechanism of low-temperature water-saturated concrete is expounded. The results show that under the same dynamic load, the dynamic stress-strain curve of saturated concrete changes obviously with the change of low temperature. The dynamic compressive strength of the natural specimen at room temperature is high while that of the water-saturated specimen is low, and the dynamic compressive strength is opposite at low temperature. At the same temperature, the energy time-history curves of concrete in the saturated state are different from those in the natural state, mainly in the plastic section. The energy time-history curves of saturated concrete are different at different temperatures, and the energy dissipation rate of saturated concrete increases linearly with the decrease of temperature. Under the experimental conditions, the dynamic strength of saturated concrete increases linearly with the decrease of temperature, and the peak strain of saturated concrete decreases linearly with the increase of temperature. With the decrease of temperature, the fragmentation of saturated concrete under the impact of the same air pressure gradually increases, and the integrity of the specimen gradually improves. Low temperature can improve the impact resistance of saturated concrete, which is consistent with the failure law of natural state concrete. The water-saturated low-temperature state of the concrete void is filled with ice crystal particles; for low-temperature water-saturated concrete in the impact of the dynamic load, the microstructure is affected by the ice crystal structure which is not easy to change; the specimen along the axial force direction microdefect development produces a crack, the crack along the parallel to the pressure direction of cracking, through the two ends of the specimen, and finally produces axial splitting tensile damage. The research results have important theoretical significance for the safety design of low temperature saturated concrete structures.